Lounging Men, Standing Women: Pose and Posture in the Aesthetic Interior - Richard W. Hayes (Cahiers Victoriens et Edouardiens)
A key moment in Henry James’s 1881 novel The Portrait of a Lady occurs when the story’s heroine, Isabel, enters the drawing room in her Roman palazzo to find her husband Gilbert Osmond seated and their guest Madame Merle standing. As several commentators have noted, Osmond violates codes of gentlemanly conduct by remaining seated while the woman stands. The simple detail of the figures’ postures criticises Osmond for his lapse in manners and adumbrates the fact that it is Madame Merle who exerts power over the novel’s main characters. The incident connects with other scenes that align Osmond, an aesthete, with furniture, cushions, and domestic décor as well with the bodily positions of sitting and resting. As Isabel observes of her husband, ‘he has a genius for upholstery’. James continues his focus on posture in his novel on the Aesthetic Movement, The Tragic Muse (1890). Published the year before Oscar Wilde’s The Picture of Dorian Gray, the novel is set, like Wilde’s, in the two most characteristic milieux of British Aestheticism: an artist’s studio and a theatre. James tells intertwined stories of a painter, Nick Dormer, and an actress, Miriam Rooth. The characters who visit Dormer’s studio are repeatedly described as lounging and reclining; ‘lolling’ is James’s preferred descriptor. Rooth, by contrast, is typically perpendicular: ‘preferring to stand’, she commands attention by a studied management of ‘the plastic quality of her person’. I propose to take a leaf from James’s attention to bodily disposition—pose and posture—to analyse interiors created during the Aesthetic Movement. My focus is on E. W. Godwin, foremost architect of Aestheticism, who is known for the artists’ houses and studios he designed in London in the 1870s and 1880s. To what extent do James’s descriptions of bodily positions in Dormer’s studio—and Wilde’s similar attention to deportment in Basil Hallward’s studio—bear similarities with Godwin’s actual interiors? Are the gender disparities underlined by James reflected in Godwin’s designs as well?